2022
DOI: 10.3390/microorganisms10112209
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteins Are Potent Activators of Nuclear Factor Kappa B in Mammary Epithelial Cells and Virulence Factors in Mycoplasma bovis Mastitis

Abstract: Mastitis due to Mycoplasma bovis is a worldwide problem, which leads to significant economic losses and affects animal welfare. However, the mechanisms by which M. bovis establishes and maintains intra-mammary infections (IMI) in dairy cows are largely unknown. To study in further detail the pathogenesis of M. bovis IMI, time- and cost-effective experimental models are needed. To this end, we established and characterized an in vitro murine mammary alveolar epithelial (EpH4) cell-based model and an in vivo mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Mycoplasma bovis strain PG45 (ATCC 25523 / NCTC 10131) (Hale et al, 1962;Wise et al, 2011) was used in this study and prepared for challenge in lactating mice as previously reported by us (Schneider et al, 2022). Bacteria were propagated at 37 o C in FF modified broth medium (Friis, 1975) supplemented with 0.5% (w/v) sodium pyruvate and 0.005% (w/v) phenol red.…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycoplasma bovis strain PG45 (ATCC 25523 / NCTC 10131) (Hale et al, 1962;Wise et al, 2011) was used in this study and prepared for challenge in lactating mice as previously reported by us (Schneider et al, 2022). Bacteria were propagated at 37 o C in FF modified broth medium (Friis, 1975) supplemented with 0.5% (w/v) sodium pyruvate and 0.005% (w/v) phenol red.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Experimental mastitis model systems were established in lactating BALB/c mice using intramammary (IMM) infusion of bacterial suspension to glands L4 and R4 (Figure 1A). We have used E. coli strain P4-NR and the type strain M. bovis PG45 as previously reported by us (Salamon et al, 2020;Schneider et al, 2022). Field strains of Strep.…”
Section: Establishment Of Murine Mastitis Model Systemmentioning
confidence: 99%
“…M. bovis mastitis is characterized by massive recruitment of neutrophils into the milk spaces of the mammary gland ( 61 ). Similarly, M. bovis has been shown to stimulate production of neutrophils extracellular traps (NETs) and possess the membrane nuclease, MnuA which degrades the NETs through either exo- or endonuclease activity ( 38 , 62 ).…”
Section: Host Immune Responses Against Mycoplasma Bovis ...mentioning
confidence: 99%
“…M. bovis mastitis is characterized by massive recruitment of neutrophils into the milk spaces of the mammary gland (61).…”
Section: Host Immune Responses Against Mycoplasma Bovis Infection 41 ...mentioning
confidence: 99%